Redefining the role of microalgae in industrial wastewater remediation - Shibsankar Mondal; Souhardya Bera; Ridipt Mishra; Subhasis Roy (Energy Nexus, 2022)
The use of microalgae for wastewater treatment is neither very new, nor a novel concept, but is understood to play a defining role in all industrial, agricultural and municipal wastewater disposal and treatment. The major advantage of phycoremediation stems from the fact that microalgae strains are capable of withstanding extremely harsh environments, which present-day industrial and municipal wastes tend to possess. The changing global outlook towards a circular bio-economy relying more on resource diversification has also led the traditional wastewater treatment processes to restructure to a low-carbon, integrated bio-refinery concept, to accommodate several waste streams. It has been well accepted among researchers regarding microalgal wastewater remediation that the meteoric rise in the interest for this area of application can be understood from the altered face of treatment. Alternatively, since the major bottlenecks of simultaneous effective nutrient assimilation and high microalgae population have been mitigated to a certain extent, microalgal wastewater treatment is now a serious contender to conventional wastewater treatment. The development in comprehensively and elaboratively characterizing effective microalgal strains for sustainable remediation has been focused, besides drawing comparisons with traditional tertiary wastewater treatment approaches. It deals more with the capability of microalgal strains to work on the toxic waste products from industrial applications in addition to assimilating non-optimum nutrient bases and conditions. Henceforth, the article dwells on the prospect of using the microalgal biomass generated to produce biofuels, bio-fertilizers, and other bio-products integral to the biorefinery concept. An important part of this work is therefore to understand the importance of microalgae in the circular bio-economy strategy with the future outlook microalgae-based waste-water remediation holds for the sustainable energy portfolio.